The impact of coronavirus on consumer behaviour in supermarket goods: the use of retail platforms/applications - Sequeira, Filipa Alexandra dos Santos (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence